The Impact Of Kampus Mengajar Program on Student Literacy Culture in Elementary School 104296 Sei Belutu - Nenni Triana Sinaga; Rika Anesia Purba; Charolina Pakpahan (Journal of Education and Teaching Learning, 2023)
Literacy and numeracy are the fundamental skills required by students to examine a reading or numbers in a variety of circumstances. According to the research findings, pupils in Indonesia still lack literacy and numeracy skills. As a result, the Ministry of Education and Culture launched a program called Teaching Campus, which invited students to participate in teaching pupils literacy and numeracy learning, particularly at the elementary school level, as part of the Freedom to Learn Campus Merdeka (MBKM) policy. Students volunteer directly to assist schools, teachers, and students based on school conditions and existing needs. Under this, Teaching Campus students conduct AKM counseling activities for fifth-grade students to strengthen reading and numeracy competencies and prepare them for the upcoming National Assessment. The goal of this research is to discover and examine how the third batch teaching campus program is implemented. This is a qualitative study using a descriptive method. During activities, data was gathered through interviews, observation, and documentation. The results demonstrated the implementation of batch 3 of the Campus Teaching Program. The development of numeracy literacy was prioritized when teaching elementary school children. Every week, different learning methods and media are used, and the literacy results show that there are still many pupils who struggle with reading, writing, and math.